Synthesis of coaxial nanotubes of polyaniline and poly(hydroxyethyl methacrylate) by oxidative/initiated chemical vapor deposition - Balkan, Alper; Armagan, Efe; Ozaydin Ince, Gozde (Beilstein Journal of Nanotechnology, 2017)
Vapor-phase synthesis techniques of polymeric nanostructures offer unique advantages over conventional, solution-based techniques because of their solventless nature. In this work, we report the fabrication of coaxial polymer nanotubes using two different chemical vapor deposition methods. The fabrication process involves the deposition of an outer layer of the conductive polyaniline (PANI) by oxidative chemical vapor deposition, followed by the deposition of the inner layer of poly(2-hydroxyethyl methacrylate) (pHEMA) hydrogel by initiated chemical vapor deposition. The vapor-phase techniques allowed for fine-tuning of the thickness of the individual layers, keeping the functionalities of the polymers intact. The response of the single components and the coaxial nanotubes to changes in humidity was investigated for potential humidity sensor applications. For single-component conductive PANI nanotubes, the resistance changed parabolically with relative humidity because of competing effects of doping and swelling of the PANI polymer under humid conditions. Introducing a hydrogel inner layer increased the overall resistance, and enhanced swelling, which caused the resistance to continuously increase with relative humidity.
Keywords: coaxial nanotubes; humidity sensors; initiated chemical vapor deposition; oxidative chemical vapor deposition; polyaniline